Pengaruh Jenis Pupuk Organik Padat Terhadap Pertumbuhan Beberapa Varietas Tanaman Terung Ungu (Solanum melongena L.) - Novidanisa Sitorus; Syarifa mayly; Lisdayani Lisdayani (Jurnal Agrotek Lestari, 2023)
Eggplant (Solanum melongena .L.) is a type of annual annual vegetable. Efforts that can be made to increase eggplant production apart from extensification, diversification and rehabilitation efforts are also through agricultural intensification efforts. One of the intensification efforts is fertilization. The use of organic fertilizers has a major influence on the physical, chemical and biological properties of the soil. The application of organic fertilizers is considered to be very supportive of efforts to increase the productivity of agricultural crops. This research was conducted in the experimental field of Alwashliyah University in Simalingkar B from August to November 2022. This research used a Factorial Randomized Block Design (RAK), Factor I, namely solid organic fertilizer (P) which consists of 5 factors including P1 = Kasgot Fertilizer, P2 = Vermicompost Fertilizer, P3 = Cow Manure, P4 = Chicken Manure, P5 = Rice Husk Biochar. Factor II is variety (V), including V1 = Mustang variety, V2 = Reza variety. The results showed that the use of organic fertilizers had a significant effect on plant height, number of leaves, stem diameter and number of primary branches. The highest eggplant plant height was in the treatment of using cassava fertilizer, which was 58.78 cm. The use of eggplant plant varieties had no significant effect on plant height, number of leaves, number of primary branches and stem diameter. The highest number of leaves was found in the Reza variety, which was 11.44 leaves.